2013
DOI: 10.1590/s0036-46652013000200002
|View full text |Cite
|
Sign up to set email alerts
|

The Schistosomula Tegument Antigen as a Potential Candidate for the Early Serological Diagnosis of Schistosomiasis Mansoni

Abstract: SUMMARYIf Schistosoma mansoni infection could be detected in its early stages, especially before the egg deposition in the host tissues, the development of severe pathologic lesions could be efficiently prevented. We therefore developed an indirect enzyme-linked immunosorbent assay based on the detection of specific IgG against schistosomula antigens (ELISA-SmTeg). The assay was applied in sera samples from non-infected and infected mice collected seven and 15 days post-infection. The results were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As the host is exposed (internally) to cercariae and schistosomula earlier than they are exposed to eggs, antigens that are highly expressed or solely expressed in one of these two stages are likely be potential candidates for early diagnosis. For example, previous studies of the schistosomula (mechanically transformed cercariae) tegument antigen revealed this antigen had diagnostic value for early infections [ 19 ]. In this study, we found that antigens SjSP-13, SjSP-160 and SjSP-216 were highly expressed in young worms, while antigens, SjSP-23, SjSP-164 and SjSP-189 were highly expressed in eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the host is exposed (internally) to cercariae and schistosomula earlier than they are exposed to eggs, antigens that are highly expressed or solely expressed in one of these two stages are likely be potential candidates for early diagnosis. For example, previous studies of the schistosomula (mechanically transformed cercariae) tegument antigen revealed this antigen had diagnostic value for early infections [ 19 ]. In this study, we found that antigens SjSP-13, SjSP-160 and SjSP-216 were highly expressed in young worms, while antigens, SjSP-23, SjSP-164 and SjSP-189 were highly expressed in eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the reactivity of antibodies against crude worm antigens remains low until the infections become patent in the experimental hosts [ 17 , 18 ]. Therefore, the ideal immunodiagnostic assay to detect early infections would use antigens from the schistosomula or cercariae [ 19 ]. However, it is notoriously difficult to extract antigens from the schistosomula or cercariae.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of antibody detection-based diagnosis in discriminating current from past infection, its high sensitivity provides advantages for detecting schistosomiasis cases in low-endemic areas [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is currently acknowledged that the KK test lacks sensitivity especially in low endemic areas [14]. The search for a reliable tool for monitoring and surveillance of schistosomiasis has led to various antigens being investigated for sero-diagnostic tests [15]: schistosomula tegumental antigens [16,17], soluble egg antigens (SEA) [18], soluble worm antigen preparation (SWAP), and cercarial transformation fluid [19,20]. Tests based on the detection of specific antibodies against these antigens provide variable advantages and drawbacks that limit their applicability [21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the available antibody detection immunoassays make use of antigens derived from the eggs and adult worms 14 , 15 . The application of schistosomula antigens as an immunodiagnostic method for early detection of Schistosoma infection has been previously explored among travelers and acute patients 10 , 12 , however, little is known about its suitability for evaluation of chronic infection.…”
Section: Introductionmentioning
confidence: 99%